The Impact of Interactive Flat Panel Displays (IFPD) on Student Engagement and Learning Motivation - Punjung Hartanto; Diah Wahyuningsih (Golden Ratio of Data in Summary, 2026)
This study examines the impact of Interactive Flat Panel Displays (IFPDs) on students’ engagement and learning motivation in elementary education at SDN 1 Sempu. Student engagement and motivation are important aspects of the learning process, particularly at the elementary school level, where meaningful and interactive learning experiences can support students’ active participation and deeper understanding. The integration of interactive technology such as IFPDs plays a strategic role in creating engaging and student-centered learning environments by combining multimedia content, touchscreen interaction, and collaborative activities. The objective of this study was to explore how the use of IFPDs influences students’ behavioral and cognitive engagement as well as their learning motivation in classroom settings. This study employed a qualitative case study approach using classroom observations, semi-structured interviews, and documentation to collect data. The participants included elementary school teachers and students at SDN 1 Sempu who had experience using IFPDs in classroom instruction. The findings revealed that the use of IFPDs enhanced students’ learning experiences through three main aspects: increased behavioral engagement during interactive activities, improved cognitive engagement through visual and interactive learning materials, and strengthened learning motivation characterized by enthusiasm and active participation. Students were more involved in touchscreen-based activities, group discussions, and interactive quizzes, which helped them focus on learning tasks and understand the material more effectively. However, the findings also indicated that the effectiveness of IFPDs depended on teacher facilitation and pedagogical integration. Teachers who designed interactive and student-centered activities were able to maximize the benefits of IFPDs, while limited technical skills and preparation time sometimes became challenges in implementation. Overall, the study concludes that the integration of IFPDs can significantly enhance student engagement and learning motivation when supported by effective teaching strategies and adequate teacher preparation. The findings contribute to the understanding of technology integration in elementary education and provide practical insights for teachers and schools in optimizing the use of interactive digital technologies in classroom learning.